Cardiorenal syndrome and diabetes: an evil pairing - Méndez Fernández, Ana Belén; Vergara Arana, Ander; Olivella San Emeterio, Aleix; Azancot Rivero, Maria Antonieta; Soriano Colome, Toni; Soler Romeo, Maria Jose (Frontiers in Cardiovascular Medicine, 2023)
Cardiorenal syndrome (CRS) is a complex disease in which the heart and kidneys are simultaneously affected, and subsequently, the malfunction of one organ promotes the deterioration of the other. Diabetes is associated with a higher increased risk for HF, and a worse prognosis. In addition, almost 40% of people with diabetes mellitus (DM) develop chronic kidney disease (CKD), making DM the leading cause of kidney failure worldwide. As expected, the combination of these three comorbidities is associated with a substantially increased risk of hospitalization and mortality. The cardiorenal units, with a multidisciplinary team (cardiologist, nephrologist, nursing), multiple tools for diagnosis, as well as new treatments that help to better control cardio-renal-metabolic patients, increasingly cover the management of patients with CRS. In the last decade, the development of new drugs such as sodium-glucose cotransporter-2 inhibitors (SGLT2s), with a cardiovascular benefit initially demonstrated in patients with type 2 DM and subsequently expanded to CKD and heart failure with and without T2DM, are offering a new therapeutic approach with potential benefits in reduction of cardiorenal adverse outcomes. Furthermore, glucagon-like peptide-1 receptor agonists (GLP-1 RAs) have shown CV benefits in diabetic patients with established CV disease in addition to a decreased risk of CKD progression.